Think and grow rich - Hill, Napoleon, e uthor (New York : Ballantine Books, 1983)
A motivational personal development and self-help classic that presents Napoleon Hill$1 (Bs philosophy of success, based on his study of famous millionaires and achievers. The book outlines thirteen principles for achieving wealth and personal fulfillment through the power of thought, persistence, and goal setting.s
Originally published in 1937.
Includes bibliographical references.
Keywords: Success; Success in business; Motivation (Psychology).